African Nannies in Paris. Women's Immigration and Domestic Work in France - (:unkn) unknown (My University, 2021)
This thesis is part of the framework of transnational female migration. Using domestic care work as a gateway, it attempts to retrace the migratory and professional trajectory of women migrant from sub-Saharan Africa working in the French capital. The aim is to understand the process of integration of these women, through a particular form of work: home-based childcare. Beyond domestic work in itself, it is the construction of an identity, punctuated by all the bifurcations inherent to migratory experience, that constitutes the central issue. Through a qualitative survey combining interviews, observations and photographic data, we reconstructed the migratory careers of these women from their countries of origin. We then studied the conditions of their arrival in France and the process by which they embarked on a career as home-based nannies. Finally, we tried to understand what this professional experience taught us about their relationship with themselves, without ever forgetting their triple condition as women, black and immigrants. Childcare work is thus seen as a form of integration from below for this category of migrants, in the same way as we have seen for certain forms of employment occupied by migrants (men) and which are socially undervalued. Investigating African nannies in Paris is also, from this point of view, contributing to a better knowledge of the future of immigrant women.
Keywords: African Research